Intellectual Humility and Self-Censorship in Higher Education; a thematic analysis - Godfrey, Hayden (Frontiers in Education, 2023)
This article explores whether social science lecturers and postgraduate students perceive their experiences of university as supporting intellectual humility - a concept representing a disposition to rigorously consider opposing ideas to beliefs held in order to confirm the positive epistemic status (or truth) of ones’ own beliefs. Forty participants (twenty lecturers and twenty postgraduate students) in the social sciences participated in semi-structured interviews centred on whether their experiences of higher education support the virtue of ‘intellectual humility’. Through a thematic analysis, results showed that experiences of both lecturers and students did not support the traits of intellectual humility. Suggestions for future research are made. The themes identified in this study could be used as a framework for investigating differing contexts of higher education in terms of their reflection of intellectual humility.